Heavy aggregate and different admixtures efffect on parquets: chrome, magnetite, and quartz-based surface hardener - Ustabas, Ilker; Erdogdu, Sakir; Ucok, Mustafa; Kurt, Zafer; Cakmak, Talip (Revista de la Construcción. Journal of Construction, 2024)
This paper presents the mechanical and micro-structure results of concrete parquet blocks. The blocks were generated by utilizing the same part in the bottom part and by substituting different proportions (40%, 30%, 20%, and 10%) of heavy aggregate like chromite aggregate, magnetite aggregate, normal aggregate, and surface hardener in the upper part. The parquet sample tests were conducted on TS 2824 EN 1338. The test outcomes indicated that utilizing diverse aggregate and chemical materials boosted the abrasion resistance, 40% magnetite and quartz-based concrete parquet block samples demonstrated the best abrasion resistance values. Also, the minimum amount of mass loss was discovered in the samples that possess high water absorption at the freezing-thaw test. The different material substitutions in the sheet of the surface of the concrete parquet block samples altered the tensile strength of the samples, even though they did not bring about an outstanding variation in the compressive strength of the concrete parquet samples.